PENGAWASAN DAN PENEGAKAN HUKUM E-COMMERCE OLEH KPPU DALAM MENGATASI PERSAINGAN USAHA TIDAK SEHAT - Anhar Sengge; Sudirman; Wahyudi Umar (CV Rewang Rencang, 2024)
This study aims to analyze the role of the Business Competition Supervisory Commission (ICC) in the supervision and enforcement of e-commerce law in Indonesia, especially in the context of unfair business competition. This study uses a normative juridical approach to evaluate the effectiveness of ICC's supervision and examine the challenges faced by ICC in implementing existing regulations, considering the ongoing dynamics of the digital market. The results of the study show that although ICC has made significant efforts in supervision, there are still legal loopholes that need to be corrected to ensure healthy business competition in the digital era. Therefore, it is important to strengthen regulations and supervisory mechanisms so that ICC can be more effective in tackling unfair business competition practices in the e-commerce sector